Naturalness perception of materials : a sensory, affective or cognitive evaluation? - Whitaker, T. Aisling (Trinity College (Dublin, Ireland). School of Psychology, 2010)
The studies reported in this thesis contribute to a new and emerging field of investigation, which focuses on the neural processes underlying pleasure, aesthetics and moral evaluations in the brain by merging this field with that of texture perception and the evaluation of materials in terms of naturalness. Research spanning many disciplines of literature demonstrates that humans possess a strong positive bond with nature, and that this relationship influences our preferences in food and landscapes, and can impact on our health and well-being (see Chapter 1).
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin.